2018
DOI: 10.1158/2326-6066.cir-17-0489
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumoricidal TCRs from Tumor-Infiltrating Lymphocytes by Single-Cell Analysis

Abstract: T-cell receptor (TCR) gene therapy is a promising next-generation antitumor treatment. We previously developed a single-T-cell analysis protocol that allows the rapid capture of paired TCRα and β cDNAs. Here, we applied the protocol to analyze the TCR repertoire of tumor-infiltrating lymphocytes (TIL) of various cancer patients. We found clonally expanded populations of T cells that expressed the same clonotypic TCR in 50% to 70% of CD137CD8 TILs, indicating that they responded to certain antigens in the tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…However, a direct functional assay of TCRs obtained from Treg cells is still not available, reflecting the limited knowledge about epitopes from physiological targets of Treg cells (27, 36). TCRs from tumor specific conventional CD4 + T cells and CD8 + T cells were identified using single-cell RT-PCR methods (23, 24, 37, 38). We also demonstrated a rapid and efficient functional assay for TCRs directly obtained from CD8 + T cells using TCR-transduced lymphocytes in the absence of information on antigen or MHC haplotype (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a direct functional assay of TCRs obtained from Treg cells is still not available, reflecting the limited knowledge about epitopes from physiological targets of Treg cells (27, 36). TCRs from tumor specific conventional CD4 + T cells and CD8 + T cells were identified using single-cell RT-PCR methods (23, 24, 37, 38). We also demonstrated a rapid and efficient functional assay for TCRs directly obtained from CD8 + T cells using TCR-transduced lymphocytes in the absence of information on antigen or MHC haplotype (38).…”
Section: Discussionmentioning
confidence: 99%
“…TCRs from tumor specific conventional CD4 + T cells and CD8 + T cells were identified using single-cell RT-PCR methods (23, 24, 37, 38). We also demonstrated a rapid and efficient functional assay for TCRs directly obtained from CD8 + T cells using TCR-transduced lymphocytes in the absence of information on antigen or MHC haplotype (38). We tried to apply this technique to mixed lymphocyte reaction of paired αβ TCR-transduced maternal T cells or TCR-negative T cell lines against self-fetal umbilical cord blood but were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the transduced T cells expressing TCRs recognized the neoantigen presented by autologous antigen-presenting cells [124] . Another study using single-cell TCR repertoire analysis revealed that clonally expanded CD8 T cells were antigen-specific and showed cytotoxic activity against tumors in mouse models [126] . Intriguingly, the combination of 10x Genomics' single cell TCR sequencing platform coupled to gene expression holds enormous potential for assessing and monitoring patient response to cancer vaccines and immunotherapy drugs.…”
Section: Tcr Repertoire Analysismentioning
confidence: 99%
“…Clonally expanded TCRαβ+ T cells were identified in patients with hematologic malignancies and cancer, and the identified tumor antigen‐specific TCRαβ gene could be used to construct TCR‐modified T cells (TCR‐T) for cancer immunotherapy . Molecular analysis, particularly using next‐generation sequencing and single‐cell sequencing, could identify clonal TCR rearrangements, confirming specifically expanded T cell clones and monitoring antigen‐specific T cell responses, which may help to design effective TCR‐based immunotherapies . However, these analyses are incapable of evaluating the functional status of clonally expanded T cells.…”
Section: Introductionmentioning
confidence: 99%
“…2,[25][26][27] Molecular analysis, particularly using next-generation sequencing and single-cell sequencing, could identify clonal TCR rearrangements, confirming specifically expanded T cell clones and monitoring antigen-specific T cell responses, which may help to design effective TCR-based immunotherapies. [28][29][30] However, these analyses are incapable of evaluating the functional status of clonally expanded T cells. Knowledge of the distribution of the TCR + subfamily in T cell subsets in patients with leukemia is lacking.…”
Section: Introductionmentioning
confidence: 99%